DAIRY PRODUCTIVITY OF QAMAR SUR SHEEP BELONGING TO THE KARAKALPAK TYPE - A. F. Astankulov (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, according to the milk yield of the qamar sur sheep belonging to the Karakalpak type, the first 30-day milk yield in sheep is 41.80-42.04% on average in the qamar variations, and in the second 30th day, 32.08-34.27%-milk was milked, and in the third 30th day, the milk yield was 23.68 - 25.76%, in comparison with the Black Qamar, it was higher by 0,2%.